Shadowmancer - Taylor, Paul Graham (New York : G.P. Putnam's Sons, 2004)
When Obadiah Demurral, the power-hungry Vicar of Thorpe, attempts to become a god by dabbling in magic, Raphah (who has come from Africa to get back the artifact stolen from his Temple and sold to Demurral) joins forces with Kate and Thomas to stop him.
Keywords: Magic -- Juvenile fiction